Cyclodextrin-Based Nanosystems as Drug Carriers for Cancer Therapy - Sivakumar, Ponnurengam M.; Peimanfard, Shohreh; Zarrabi, Ali; Khosravi, Arezoo; Islami, Matin (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background and Objective: Cyclodextrins have been of great interest as excellent candidates for fabricating versatile nano-drug delivery systems due to their commercial availability, easy functionalization, low immunogenicity, biocompatibility and safety. The possibility of reversible inclusion complex formation between cyclodextrins and various guest molecules in association with versatile exclusive properties of cyclodextrins offer a route towards the fabrication of highly sophisticated nanostructures with enormous potential for cancer treatment. Methods and Results: The current review discusses important recent advances in the fabrication and development of cyclodextrin-based nanostructures for cancer therapy. Firstly, the formation of inclusion complexes between cyclodextrin derivatives and anticancer compounds, as well as their application, are summarized. Secondly, the cyclodextrins -based nanosystems including cyclodextrin-containing polymers, cyclodextrin-based supramolecular necklaces, which consist of polyrotaxanes and polypseudorotaxanes and cyclodextrin based hydrogels accompanied by their applications in cancer treatment are highlighted. In the end, the future perspective of this field is discussed. Conclusion: Numerous investigations in this area pave the way for the flourishing of the next generation of nano-therapeutics towards enhanced cancer therapy.
Keywords: drug delivery